2021
DOI: 10.1016/j.ijscr.2021.106328
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone ileus associated with cholecystogastric fistula: Case report, diagnosis and surgical treatment

Abstract: Introduction Gallstone Ileus is a rare complication of cholelithiasis, associated with multiple episodes of cholecystitis, with the formation of adhesions and fistulas between the gallbladder and adjacent organs. Its diagnosis is difficult, requiring complementary imaging tests such as computed tomography or radiography. Presentation of case Female patient, with intestinal obstruction for 7 days, associated with abdominal pain and previous episodes of pain in the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
1
0
6
Order By: Relevance
“…Deve-se à presença de cálculos biliares que exercem pressão contínua e recorrente na vesícula biliar, levando à inflamação crónica com consequente erosão da parede da mesma, sendo que, posteriormente, ocorre a formação de fístula para o sistema gastrointestinal [1,5]. Apesar de uma condição rara, após excluídas as patologias mais frequentes, o diagnóstico deve ser equacionado num adulto mais velho, sem cirurgias abdominais prévias, com antecedentes de litíase biliar, que recorra ao SU por quadro de dor abdominal associada a vómitos [6,7]. No caso apresentado, os sintomas típicos de oclusão intestinal alta não são tão evidentes.…”
Section: Discussionunclassified
“…Deve-se à presença de cálculos biliares que exercem pressão contínua e recorrente na vesícula biliar, levando à inflamação crónica com consequente erosão da parede da mesma, sendo que, posteriormente, ocorre a formação de fístula para o sistema gastrointestinal [1,5]. Apesar de uma condição rara, após excluídas as patologias mais frequentes, o diagnóstico deve ser equacionado num adulto mais velho, sem cirurgias abdominais prévias, com antecedentes de litíase biliar, que recorra ao SU por quadro de dor abdominal associada a vómitos [6,7]. No caso apresentado, os sintomas típicos de oclusão intestinal alta não são tão evidentes.…”
Section: Discussionunclassified
“…Clavien et al reported the size of gallstone obstruction from 2 to 5 cm. [3][4][5] Diagnosis can be challenging due to several factors: the intermittency of symptoms, the fact that signs and symptoms are nonspecific, the advanced age of the patients and their concomitant diseases. 4 In our case, we had an atypical presentation as it was a woman younger than usual, as well as the finding of a larger stone than the average reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, cada conducta quirúrgica se debe indicar según el estado clínico del paciente y condiciones preexistentes [1,6,8] (Figura 4). En los casos en que el paciente esté hemodinámicamente inestable, sea mayor de 70 años, tenga baja reserva respiratoria, estado ASA III o IV o cualquier otro signo de gravedad, podemos utilizar inicialmente la cirugía urgente (Enterolitotomía) [19] . La enterolitotomía con colecistectomía y reparación de fístula diferidas(4-24 semanas) [8,11] , tiene menor mortalidad (11,7 vs 16,9 %), en comparación con la cirugía en un solo tiempo [1,3,8,13] , sin embargo, presenta hasta un 5 % de recidiva [1,[6][7][8] , que generalmente se presenta durante los primeros 6 meses posteriores a la operación inicial [15] .…”
Section: Discussionunclassified
“…Al momento, no existe una definición o consenso sobre cuál es la mejor opción para el tratamiento del IB, lo que debe evaluarse caso por caso, según cada paciente [19] . En nuestro caso, por las condiciones clínicas del paciente, comorbilidades y hallazgos intraoperatorios, se decidió realizar una cirugía en dos tiempos (enterolitotomía) [3,4,6,7,9,10,12] , dejando la colecistectomía y cierre de fístula para un segundo momento.…”
Section: Discussionunclassified